Bye bye Collision! Efficiency of Schedule Management with SIM-DRaW (Management Information System of Lecturer, Room, and Time) - Muhammad Nugraha; Yogi Nugraha (Universitas Darussalam Gontor, 2018)
Lectures schedule management in campus is an important aspect that must be implemented in every period. The schedule will be managed well if avoided from collision of the room, time, and lecturer. To overcome collision problem it's necessary to make mitigate system to avoid schedule changes frequently caused by collision of room, time, and lecturer. Thus, the author design and build SIM-DRaW (Sistem Informasi Manajemen Dosen, Ruang, dan Waktu) web-based to fulfill needs and overcome schedule management system. The final result of the design and build SIM-DRaW is implemented information system that can help schedule manager to avoid collision earlier.